Pengaruh Kreasi Media Botol Bekas Terhadap Kreativitas Anak Usia Dini Di Taman Kanak-Kanak - Lareza, Fifia; Rakimahwati, Rakimahwati (Jurnal Pendidikan AURA (Anak Usia Raudhatul Atfhal), 2023)
Creativity is a potential that needs to be developed in children from an early age. Early childhood creativity is a cognitive process that arises from the 4Ps, namely the person, the driver, the process, and the product. One of the media that can be used to develop children's creativity is used bottle media. This research is motivated by the problem of children's creativity, children are less skilled in working and expressing feelings. Based on the researcher's observations, the problem is due to the limited ability of teachers in designing learning media and designing learning activities. This study aims to examine the effect of used bottle media creations on the creativity of early childhood at Pembina Kindergarten 01 Ranah Ampek Hulu Tapan. This type of research is quantitative with a quashi experimental design. The research population was 49 children, while the research sample was in class B1 with 11 children as the experimental class and 11 children in B2 as the control class. This research instrument consists of five items with an assessment of BB (1), MB (2), BSH (3) and BSB (4). The data analysis technique used several tests namely, normality, homogeneity and hypothesis tests (t-test). The results of this study indicate that there is an influence of used bottle media on the creativity of early childhood creativity in Pembina Kindergarten 01 Ranah Ampek Hulu Tapan.Keywords: used bottles, creativity, early childhood